Understanding social media usage and engagement among women to inform breast cancer knowledge and prevention practices: Cross - sectional study in Delhi -National Capital Region of India - Nibha Sinha; Alka Sharma (Wolters Kluwer Medknow Publications, 2021)
Background: Breast cancer is the major concern worldwide and in India too. Lack of awareness is one of the causes of increasing mortality rate in India. Social media is playing an important role in health communication including breast cancer information. In India, number of women are using social media. Objective: To explore the impact of social media usage and engagement in enhancing knowledge and practices to prevent breast cancer among women of India. Methodology: A cross-sectional study was conducted in Delhi-National Capital Region of India with a sample of 649 women (response rate 83.51%). The questionnaire consisted of three sections. In first section, sociodemographic details (four items) were collected, second section contained five items on social media use and engagement and third part included items on knowledge about risk factors (seven items), symptoms (eight items), and screening (six items) of breast cancer and practice (seven items). Descriptive statistics, Chi-square, Cramer-V test, and structural equation modeling-Analysis of a moment structure were used to identify the relationship between social media engagement and knowledge and practices of women. Results: Around 80% (431/542) of women have medium level of social media engagement and 20% are highly engaged. The slope coefficient of the relationship between social media engagement and knowledge is 0.805 and between knowledge and practice is 0.309, Chi-square value is 52.053 and 29.624, Cramer-V statistics is 0.310 and 0.165, respectively, which indicates significant relationship. Conclusion: The study result justified significant impact of social media engagement on knowledge and practices of women to prevent breast cancer.